(untitled) (Journal of Oriental Studies, 2017)
This article discusses the contemporary British historiography of the Eurasian integration processes. The objective of this research work is to reveal the essential nature of the opinion of the British experts of modern integration processes in the Eurasian area. In the research process was identified two general views of British scholars: first expert group gives a positive assessment of the emergence and development of Eurasian integration and positive about the idea of integration on post-soviet area; second expert group critically assesses the effectiveness, potential and future opportunities of integration processes in the Eurasian area.